Trends of area, production and productivity of spices in the northeastern region - Sharma, A (Journal of Spices and Aromatic Crops, 2015)
The present study was undertaken to analyze the trends in area, production and productivity of major spices in the northeastern (NE) region. The study was based on secondary data from 1982-83 to 2011–12. The data was collected from several government publications and web sites. To analyze the trend of area, production and productivity of major spices in NE region, the linear, quadratic and exponential functional forms were used. To fit the trend, exponential functional form was used due to its higher R2 value as compared to other two forms. Besides these, compound growth rate, coefficient of variation and instability index was also estimated. The effects of area, productivity and their interaction towards increasing production were also estimated. The cultivation of spices was not risky in the NE region as revealed by the lower coefficient of variation. The coefficients of variation (CV) of area, production and productivity of spices were less than 4.16%. The instability indices for area, production and productivity for spices in the NE states were positive, which indicated less variation in growing spices in the region.